2011
DOI: 10.1007/s10695-011-9530-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of endosulfan on the haemato-immunological and histopathological responses of a threatened freshwater fish, spotted murrel, Channa punctatus

Abstract: Two experiments, one short-term and one long-term, were conducted to elucidate the acute and chronic effects, respectively, of endosulfan exposure on the haemato-immunological and histopathological responses of Channa puncatatus. In the short-term study, fish were exposed to sublethal endosulfan (8.1 μg l(-1)) for 12, 24, 36, 48, 72 and 96 h. In the long-term study, fish were fed with normal diet and simultaneously either exposed to endosulfan (1.2 μg l(-1)) for 90 days or not. Results showed that the ascorbic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Change in the diameters of the nuclei of hepatocytes can be considered a response to a stressor, and is indicative of activation of liver function as a result of increased metabolic activity against adverse conditions (Langiano Vdo and Martinez, ; Sarma et al, ; Benze et al, ). On the other hand, a decrease in the size of the nuclei can be related to the possible multiplication of hepatocytes during the replacement of damaged cells (Braunbeck et al, ; Gul et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Change in the diameters of the nuclei of hepatocytes can be considered a response to a stressor, and is indicative of activation of liver function as a result of increased metabolic activity against adverse conditions (Langiano Vdo and Martinez, ; Sarma et al, ; Benze et al, ). On the other hand, a decrease in the size of the nuclei can be related to the possible multiplication of hepatocytes during the replacement of damaged cells (Braunbeck et al, ; Gul et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypertrophy of hepatocytes in our experiments without acclimation/without food and with acclimation/without food can also be associated with contaminants (Arnold et al, ). Furthermore, other studies report that cell change may be due to structural changes related to hepatocyte cell function (Oliveira Ribeiro et al, ; Nowak and Kingsford, ), physiological conditions related to reproduction (Wester, ; Wolf et al, ), and the increased metabolic activity due to pollution (Takashima and Hibiya, ; Nowak and Kingsford, ; Sarma et al, ). In the present study, the observed changes in cell diameters show that there were physiological effects on the adaptive response of cells to the new environment in which the fish were exposed to Thiodan ® , as shown by the impact on liver function in exposed females compared to the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotopic analyses can reveal information about resource use and resource partitioning among species and is also able to determine diet and habitat use [15,17]. Here, we will address: (1) whether stable isotope values permit identification of resource use and partitioning among horse species and (2) if resource use and partitioning are determined, do the results support the ecology predicted by morphology or body size?…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study with fresh water fish, spotted murrel, channa punctatus, endosulfan produced alteration in liver histology with a fall in ascorbic acid levels. [25] Increase in lactate dehydrogenase activity with a concurrent rise in lipid peroxidation level is an indicator of cell membrane leakage and dissociation of intercellular connections due to the oxidative stress on exposure to endosulfan. Similar results have been reported earlier with insecticide aldrin, dieldrin, and endosulfan in culture cells with fractions of their lethal dose.…”
Section: Discussionmentioning
confidence: 99%